Superficial Acral Fibromyxoma: Report of 13 Cases With New Immunohistochemical Findings. (January 2017) - Cullen, Daniella; Díaz Recuero, José Luis; Cullen, Roberto; Rodríguez Peralto, José Luis; Kutzner, Heinz; Requena, Luis
Abstract : Background: Superficial acral fibromyxoma (SAF) is a benign, soft tissue neoplasm preferably located on the digits. Methods: We collected 13 cases of SAF and evaluated their clinical, histopathologic, and immunohistochemical features. Results: This study included 9 males and 4 females, median age 54 years. The patients presented with a solitary asymptomatic or tender mass, most of them arising on fingers or toes. Histopathologically all lesions consisted of nonencapsulated dermal nodules, composed of spindled cells with variable myxoid and/or fibrotic stroma. Some lesions were well circumscribed (6/12, 50%), whereas other ones appeared poorly demarcated (6/12, 50%). The stroma was predominantly myxoid (53%), myxoid-collagenous (31%) or mostly collagenous (15%). Neoplastic cells expressed immunoreactivity for CD34 (8/11), CD99 (9/12), and nestin (7/7); whereas MUC4 (0/11) and Bcl-2 (0/7) resulted negative. Conclusions: Nestin is the best immunohistochemical marker for SAF with higher sensitivity than CD34, although nestin is also positive in dermatofibrosarcoma protuberans and therefore is not helpful in differential diagnosis between SAF and dermatofibrosarcoma protuberans. Cellular digital fibromas and acquired reactive digital fibroma probably are neoplasms closely related to SAF. The homogeneous reactivity for CD99, the negativity for Bcl-2 and lack of the honeycomb infiltration of the subcutis help to rule out myxoid dermatofibrosarcoma protuberans, whereas the negativity for MUC4 and Bcl-2 are helpful tools to rule out low-grade fibromyxoid sarcoma and spindled-cell lipoma, respectively.